Pola Spasial Pergeseran Pusat Pertumbuhan Desa di Kabupaten Kulon Progo - Rahayu, Dina; Muta'ali, Luthfi (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Kulon Progo is a poorest district and has the highest development inequality in Daerah Istimewa Yogyakarta (DIY) based on Badan Pusat Statistik (BPS) publication. The local government has made various efforts to overcome the problems, one of which is by establishing growth centers since 2003. However, Kulon Progo Regency has experienced rapid development with the existence of Yogyakarta International Airport, which affected the dynamics of regional growth centers. The purpose of this study is to identify the potential Rural Growth Center (PPD) and identify the spatial patterns of PPD shifts in Kulon Progo to see the trickle down effect. This study used descriptive quantitative methods using scalogram index, centrality index, urban network analysis, and gravity index, also moran’s I index and Local Indicator Of Spatial Association (LISA). The results showed that there was a shift in rural growth centers, but the spatial analysis did not show any trickle down effect from rural growth centers that had been formed before. However, new centers were formed that were not related to the previous rural growth centers. These results indicates that the rural growth centers in Kulon Progo cannot have a growth effect on the surrounding area.